(untitled) (Central Medical College Journal, 2022)
To find out different presentations of Psoriasis in Bangladesh. Material and Methods: This is a cross sectional study of all dermatology patients with features of psoriasis who attended the dermatology outpatient clinic of the hospital between July 2016 and June 2017. Data was collected on a perform questionnaire. Age, gender and clinical presentations were recorded and analyzed using SPSS version 16. Results: Psoriasis was found in 1.13% (60/5505) of the study population. There was a male preponderance with a male to female ratio of 1.34:1. The majority of patients seen were in the fourth decade of life. Stress, alcohol, and drugs were the most reported predisposing factors to psoriasis. All types of psoriasis were found, and plaque psoriasis was the most common. Conclusion: Psoriasis is a one of the common skin diseases with wide range of clinical variation and predisposing factors. The current trend in the management of psoriasis is focused on treating the inflammatory process as well as managing the modifiable environmental triggers. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 102-105